2016
DOI: 10.1186/s12906-016-1399-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of therapeutic potentials of plant extracts against poultry bacteria threatening public health

Abstract: BackgroundPlant extracts were evaluated on poultry bacteria known to be threatening public health. This is to develop better bio-therapeutic agents from plant origin.MethodsBacteria were isolated from water, feed, crop, gizzard and faeces of layer chicken. Isolates of interest (Escherichia coli, Salmonella enteritidis, Pseudomonas aeruginosa and Klebsiella oxytoca) were subjected to antibiotic susceptibility test. Resistant strains were further evaluated against different plant extracts in comparison to Merope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
(41 reference statements)
2
19
0
1
Order By: Relevance
“…These findings were close to that (20%) reported earlier in India [1]. Many studies showed different prevalence rates of P. aeruginosa isolates in broilers worldwide: in Iraq, a low rate of 6% was reported [33], while in Nigeria, a high rate of 75% was reported [34]. These differences in prevalence rates may reflect the considerable disparity in the sampling scheme, sample types, pseudomonas detection protocol, and geographic location.…”
Section: Discussionsupporting
confidence: 86%
“…These findings were close to that (20%) reported earlier in India [1]. Many studies showed different prevalence rates of P. aeruginosa isolates in broilers worldwide: in Iraq, a low rate of 6% was reported [33], while in Nigeria, a high rate of 75% was reported [34]. These differences in prevalence rates may reflect the considerable disparity in the sampling scheme, sample types, pseudomonas detection protocol, and geographic location.…”
Section: Discussionsupporting
confidence: 86%
“…However, most vaccination programs are strongly biased toward the prevention of viral diseases. In recent times, more research has been emerging on the potential value of using plant extracts to control bacterial diseases in poultry ( 128 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is in this perspective that the hydro-ethanolic extract of Canarium schweinfurthii has been explored for its antisalmonellal activity and its bioactive compounds. Several plants are traditionally used against human salmonellosis [41][42][43][44][45][46] and avian salmonellosis [24][25][26]47]. Plants with high anti-salmonellal potential that show promise for the control of avian salmonellosis include Aloe secundiflora [47], Thymus vulgaris [48], Curcuma longa and Scutellaria baicalensis [25] and Erica mannii [27].…”
Section: Discussionmentioning
confidence: 99%
“…The large majority of salmonellosis in humans is carried by foodstuffs; mainly those of avian origin [10,20,21], therefore controlling avian salmonellosis by using plant could significantly reduce the prevalence of human gastroenteritis [20]. Several studies have focused on medicinal plants as new control strategies for human salmonellosis [22,23] or avian salmonellosis [24][25][26][27][28]. But, to our knowledge, no phytomedicine has yet been formulated to control avian salmonellosis.…”
Section: Introductionmentioning
confidence: 99%